2010
DOI: 10.1109/tnn.2009.2034741
|View full text |Cite
|
Sign up to set email alerts
|

A Multiobjective Simultaneous Learning Framework for Clustering and Classification

Abstract: Traditional pattern recognition involves two tasks: clustering learning and classification learning.Clustering result can enhance the generalization ability of classification learning, while the class information can improve the accuracy of clustering learning. Hence, both learning methods can complement each other. To fuse the advantages of both learning methods together, many existing algorithms have been developed in a sequential fusing way by first optimizing the clustering criterion and then the classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…For the reason of preferring a cross entropy loss rather than directly using the MSE loss as the clustering cost, please refer to "Algorithmic Details of the Proposed Method" part of this study. Cross entropy calculation is given in Equation (7). Since all elements of y are zero, Equation ( 7) simplifies to Equation ( 8).…”
Section: Clustering Costmentioning
confidence: 99%
See 2 more Smart Citations
“…For the reason of preferring a cross entropy loss rather than directly using the MSE loss as the clustering cost, please refer to "Algorithmic Details of the Proposed Method" part of this study. Cross entropy calculation is given in Equation (7). Since all elements of y are zero, Equation ( 7) simplifies to Equation ( 8).…”
Section: Clustering Costmentioning
confidence: 99%
“…The result of the experiments, a robust framework which is capable of clustering and classifying a dataset simultaneously has been asserted as the output of their study. Additionally, in Cai et al [7], the authors advanced their framework to employ multiple objective functions for clustering and classification rather than a single one. Qian et al [8] addressed the problem of high complexity in the objective function that is suggested by [6,7] and proposed a new framework that exploits cluster structure representations instead of cluster posterior probabilities of classes to relate clusters and classes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation